Antibiotic-related meanings, experiences and information sources of women in the economic margins of urban Manila. Issue 1 (7th November 2018) - Bernadas, Jan Michael Alexandre Cortez
Abstract : Purpose: Drawing insights from the culture-centered approach (Dutta-Bergman, 2004; Dutta, 2007), the purpose of this paper is to explore the meanings of, experiences with, and information sources for antibiotics among at-risk yet understudied populations in urban and economic margins in the Global South. Design/methodology/approach: Given the exploratory purpose of this paper, it used qualitative approach specifically focus group discussions with mothers, guardians and female senior citizens from Manila, Philippines. Findings: Antibiotics had multiple meanings – from purposes and modes of acquisition to side-effects. Experiences with antibiotics were not only tied to financial difficulties, but also in administering antibiotics to children or wards and managing side-effects. Furthermore, medical doctors were the most accessed and preferred sources of antibiotics-related information. Originality/value: To date, this paper is one of the few to argue that knowing the conditions into which antibiotics are situated in the Global South is critical for strengthening global public health campaigns and policies against antimicrobial resistance a and reducing global health inequity.